2020 Virtual K-State First Celebration - K-State First (My University, 2021)
In a virtual celebration, K-State First presents the winners for the 2020 First-Year Student Advocate and K-State First Book awards. The 2020 First-Year Advocate Award winners: Faculty/staff recipient - Jessica Henault Student recipient - Julia Gross K-State First Book Awards: Faculty/staff recipient - Suzanne Porath Student group recipient - Minorities in Agriculture, Natural Resources and Related Sciences or MANRRS Student recipients - Grace Huynh and Bailey Roberts
Keywords: CAT communities; Awards; Common reading program; Engagement